Antibacterial and Cytotoxic Phenolic Polyketides from Two Marine-Derived Fungal Strains of Aspergillus unguis - Cao Van Anh; Joo-Hee Kwon; Jong Soon Kang; Hwa-Sun Lee; Chang-Su Heo; Hee Jae Shin (MDPI AG, 2022)
A chemical investigation on the EtOAc extracts from two marine-derived fungal strains of Aspergillus unguis resulted in the isolation of three previously undescribed phenolic polyketides including unguidepside C (1), aspersidone B (3), and agonodepside C (12), and their 14 known congeners. The structures of the new compounds were determined based on detailed analysis and comparison of their spectroscopic data with literature values, as well as Snatzke's method. The new compounds (1, 3, and 12) displayed a significant anti-Gram-positive bacterial activity, with MIC values ranging from 5.3 to 22.1 µM. Additionally, the isolated compounds (1-11 and 13-16) were evaluated for their cytotoxicity against a panel of tumor cell lines. Most of them (except for 9) displayed cytotoxicity against all the tested cell lines, with IC50 values ranging from 2.5 to 46.9 µM.